Relationship Between Medication Adherence Level and Recovery of Pulmonary Tuberculosis Patients at Gapura Public Health Center Sumenep - Maulina Syafakamila; Rini Purbowati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis (MTB).  Regarding this, Indonesia is ranked second globally in terms of tuberculosis prevalence.  TB cases in Sumenep Regency are increasing every year.  The high incidence of TB in Sumenep mostly is caused by the patients' lack of adherence to taking medication.  The level of compliance in taking drugs can be influenced by several factors including age, educational level, and gender. This study aimed to ascertain the association between medication adherence and recovery in patients with pulmonary tuberculosis at the Gapura Public Health Center Sumenep. This study employed an analytical observational design with a cross-sectional approach, utilizing secondary data from medical records and TB.01 treatment cards. The population in this study consisted of 40 individuals. Total sampling is used to choose samples. The study's findings revealed that most patients 62.5%  were male, 37.5% were between the ages of 26-45, 15% were from Gapura Barat, 35% had an elementary school education, and 55% were farmers. As many as 90% of patients adhere to treatment and 87.5% recover. Additionally, statistical tests yielded a p-value of <0.001. The study concludes a correlation between medication adherence and recovery of patients with pulmonary tuberculosis at the Gapura Public Health Center Sumenep. It is advised that health personnel maintain as many programs as possible, including counseling, home visits, and remote monitoring via telecommunications.